PERBEDAAN AMITOSIS, MITOSIS DAN MEIOSIS PADA MATERI GENETIKA DAN REPLIKA DNA - Shafitri, Shafitri; Mustakim, Ardi (Medic Nutricia : Jurnal Ilmu Kesehatan, 2025)
Analyzes Amitosis, Mitosis and Meiosis Genetic Materials and DNA Replicas. This research uses qualitative methods and combines empirical data with relevant theory through a descriptive approach. A library study approach is used to collect secondary data from various sources, including books, journals, scientific articles and online media. The findings show 1) Amitosis, as a simple process, is involved in the growth and maintenance of cells in simpler organisms, while mitosis is important for the growth, repair and maintenance of tissues in the body. On the other hand, meiosis is a special process that occurs during sexual reproduction, producing reproductive cells with a haploid set of chromosomes necessary for the union of reproductive cells of different sexes. 2) These differences ensure that organisms can grow, develop, and produce efficiently and accurately. Thus, understanding the mechanisms of DNA replication and cell division processes becomes important in the context of cell biology, genetics, and the evolution of organisms.